(untitled) (Journal of Applied Oral Science, 2007)
Quantification of the expectation of craniofacial growth during the pubertal growth spurt (PGS) is helpful in orthodontic diagnosis and treatment planning. Thus, this study investigated whether the stages of the vertebral maturation index (VMI) would be valid for estimating cranial and mandibular growth during the initial stages of PGS, testing the null hypothesis that these structures do not demonstrate differential growth dependent on the maturation stage. A study population of 45 patients of both genders with 2 lateral cephalometric radiographs, taken at a 12-month interval, was selected from files. All patients should not have been previously submitted to orthodontic treatment and should be before or during the peak stage of PGS. The S-N and Co-Gn cephalometric measurements were traced on both radiographs of each patient, by computed cephalometric tracings, for evaluation of skull and mandible, respectively. The growth of these structures was established by the difference between the measurements obtained on both tracings. The VMI stage was also estimated on the radiographs, determining the position of patients on the PGS curve at two periods, baseline and after 12 months. Cephalometric tracings and VMI estimates were performed by two calibrated examiners. Descriptive statistics revealed that both cephalometric measurements increased during the study period, especially Co-Gn, which demonstrated (ANOVA and Tukey's test; 5% significance level), a statistically significant peak of development (p = 0.001), when the patient was in the VMI stage representing the PGS peak. It was concluded that the VMI stages were valid for the analysis of cranial growth and especially of mandibular growth at the initial stages of PGS, thus rejecting the null hypothesis.